Literature Review : Tatalaksana Mioma Uteri - Fatahillah, Fatahillah; Hanriko, Rizki; Septiani, Linda; Sari, Ratna Dewi Puspita (Medula, 2024)
Myoma or uterine fibroids are benign tumors that often occur in the uterine wall. Myomas can be asymptomatic or cause symptoms such as abnormal bleeding, pelvic pain, and disorders of the urinary tract. Risk factors include age, race, age of menarche, parity, family history, hormonal contraceptive use, and obesity. Diagnostic examination involves pelvic examination, ultrasound, hysteroscopy, and MRI. Medical therapies used such as NSAIDs, oral contraceptives, Levonorgestrel-releasing intrauterine system (Mirena), tranexamic acid (cyclocapron), GnRH agonists and SPRMs and surgeries such as myomectomy, hysterectomy, uterine artery embolization, and MRgFUS. Management of Myoma must consider various factors, namely tumor size, patient age, symptom and the desire to maintain fertility in order to provide optimal treatment according to the patient's needs and preferences.